Gestión del inventario según la nic 2 en el supermercado Megapropinec de la ciudad de Babahoyo, 2021. - Acosta Janetta, Ileana Michelle (2022)
This case study was carried out in the Megapropinec supermarket in the city of Babahoyo, where weak inventory control was identified; therefore, the objective of the study is to determine the inventory management in the Megapropinec supermarket. The methodology consisted of a mixed approach (quali-quantitative), types of field and documentary research, a cross-sectional study with a descriptive scope, the inductive method, the techniques were interview and direct observation; In addition, the investigative instruments were made up of an interview and an observation sheet. The results were: there is no inventory control during the supply process to verify the existence of certain products with the operating system; sometimes there are economic losses because the goods do not rotate properly and expire; the inventory control method is carried out through the Dobra Business Management System; Regarding the rotation per day, it had a high rotation of its stocks due to the fact that they sell wholesale and their supply is weekly. In conclusion, the correct management of the inventory allows obtaining some advantages such as knowing the products with the highest and lowest rotation, identifying the real value of the inventory account and making adequate decisions in relation to supply. The inventory rotation in the supermarket is good and it rotates its products every 15 days. The accounting treatment of inventory does not adhere to the guidelines of IAS 2.